PENGEMBANGAN MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL KOTA PALEMBANG MATERI MAKANANKU, BUDAYAKU KELAS II SD - Fitri Nur Sania; Maharani Oktavia; Puji Ayurachmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop flashcard media based on local wisdom of Palembang city with the material of my food, my culture for grade II of elementary school that is valid and practical. This type of research is Research and Development (R & D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were grade II students of Elementary School 90 Palembang. Data collection techniques used were interviews, questionnaires, and documentation. Data analysis techniques consisting of validity and practicality. Validity analysis conducted by three experts, namely language experts, material experts, and media experts with an average value of 87.7% in the very valid category. Practicality analysis of teacher responses was 92.8% in the very practical category, practicality of the average value of one to one trials was 95.3% in the very practical category, the small group trial stage obtained an average value of 94% in the very practical category and the large group trial stage obtained an average value of 88.4% in the very practical category. So it can be concluded that the development of flashcard media based on local wisdom of Palembang city on the subject of my food, my culture for grade II elementary school is stated to be very valid and very practical.